Mitigation of intestinal autofluorescence accumulation in Caenorhabditis elegans treated with plant-based natural products - S. S. Salimon; E. I. Marusich; S. V. Leonov; M. V. Pustovalova (Acta Biomedica Scientifica, 2024)
Introduction. Aging is a complex process related with the gradual diminution in cellular and physiological functions. The geroprotective effect of 10 biologically active substances (BASs) – rutin, squalene, kaempferol, biochanin A, ursolic acid, chlorogenic acid, baicalin, mangiferin, quercetin and trans-cinnamic acid and 5 crude extracts (Ginkgo biloba L., Pulmonaria officinalis L., Scutellaria baicalensis Georgi, Hedysarum neglectum Ledeb. and Panax ginseng C.A. Mey) isolated from medicinal plants of Altai Region of Russia were evaluated for their influence on the accumulation of intestinal autofluorescence material (IAM) using Caenorhabditis elegans model.The aim of  the  study. IAM facilitates age-related decline and is a non-intrusive biomarker of senescence. This study assessed the impact of different bioactive substances in reducing the build-up of IAM using C. elegans model.Materials and methods. Gravid nematodes were synchronized, and then seeded in 96-well plates to develop to L4-stage. Each BAS in 200 µM, 100 µM, 50 µM and 10 µM concentrations and extracts with a tenth, hundredth and thousandth times-dilution were administered to each well in 6 replicates for each treatment group. On incubation days 1, 5, and 15, adult L4 nematodes underwent spectrofluorometric analysis to determine the effect of the BASs and extracts on IAM accumulation.Results. It was found that quercetin, kaempferol, baicalin, mangiferin, G. biloba and P. officinalis extracts exhibited the most profound inhibition of IAM accumulation compared to the control. It was noteworthy that the 10  µM concentration of  mangiferin significantly inhibited IAM accumulation in a manner comparable to the 200 µM of baicalin and 100 µM of quercetin. In addition, the crude extracts of G. biloba and P. officinalis respectively exhibited 2.8- and 1.8-fold decrease in IAM accumulation.Discussion. The accretion of IAM is inversely proportional to longevity. Thus, the BASs identified in this study to modulate IAM accumulation could serve as important precursors or active ingredients for the pharmacosynthesis of geroprotective drugs in future research.